Residues of bosonic string scattering amplitudes and the Lauricella functions - Sheng-Hong Lai; Jen-Chi Lee; Yi Yang (Nuclear Physics B, 2023)
We calculate explicitly residues of all n-point Koba-Nielsen (KN) amplitudes by using on-shell recursion relation of string scattering amplitudes (SSA). In addition, we show that the residues of all SSA including the KN amplitudes can be expressed in terms of the Lauricella functions. This result demonstrates the exact SL(K+3,C) symmetry of the tree-level open bosonic string theory. Moreover, we derive an iteration relation among the residues of a given SSA. This iteration relation is related to the SL(K+3,C) symmetry and can presumably be used to soften the well-known hard SSA.